Genome-wide identifcation, characterization and expression profles of the CCDgene family in Gossypiumspecies - Zhang, Shulin; Guo, Yutao; Zhang, Yanqi; Guo, Jinggong; Li, Kun; Fu, Weiwei; Jia, Zhenzhen; Jia, Zhenzhen; Lam-Son Phan Tran; Jia, Kun-Peng; Miao, Yuchen
Carotenoid cleavage dioxygenases (CCDs)are a group of enzymes that catalyze the selective oxidative cleavage steps from carotenoids to apocarotenoids, which are essential for the synthesis of biologically important molecules such as retinoids, and the phytohormones abscisic acid (ABA)and strigolactones. In addition, CCDs play important roles in plant biotic and abiotic stress responses. Till now, a comprehensive characterization of the CCDgene family in the economically important crop cotton (Gossypiumspp.)is still missing. Here, we performed a genome-wide analysis and identifed 33, 31, 16 and 15 CCDgenes from two allotetraploid Gossypiumspecies, G. hirsutumand G. barbadense, and two diploid Gossypium species, G. arboreumand G. raimondii, respectively. According to the phylogenetic tree analysis, cotton CCDs are classifed as six subgroups including CCD1, CCD4, CCD7, CCD8, nine-cis-epoxycarotenoid dioxygenase(NCED)and zaxinone synthase(ZAS)sub-families. Evolutionary analysis shows that purifying selection dominated the evolution of these genes in G. hirsutumand G. barbadense. Predicted cis-acting elements in 2 kb promoters of CCDs in G. hirsutumare mainly involved in light, stress and hormone responses. The transcriptomic analysis of GhCCDs showed that diferent GhCCDs Displayed diverse expression patterns and were ubiquitously expressed in most tissues; moreover, GhCCDs displayed specifc inductions by diferent abiotic stresses. Quantitative reverse-transcriptional PCR (qRT-PCR)confrmed the induction of GhCCDs by heat stress, salinity, polyethylene glycol (PEG)and ABA application. In summary, the bioinformatics and expression analysis of CCDgene family provide evidence for the involvement in regulating abiotic stresses and useful information for in-depth studies of their biological functions in G. hirsutum.
Keywords: CCDGENES; COTTON; GENOME-WIDE ANALYSIS; PHYLOGENETIC TREE; ABIOTIC STRESSES; EXPRESSION ANALYSIS